Application of Wizard in Website Design - Muhammad Fauzi; Yudi Yudi; Frinto Tambunan; Frans Ikorasaki (JUDIMAS, 2021)
The website is a digital information medium, a website created in the form of a graphical user interface with several programming languages that are summarized for the concentration of the web design stage, in this case a problem arises about the difficulty of learning programming languages, it takes quite a lot of time, therefore the author introducing a wizard as a website design that even ordinary people can also make by this servant is carried in SMK Penerbangan Medan by several people in 1 team which is divided into each. To make website design easier, faster, more efficient and a more structured system, where websites are created in a wizard and the system is provided by vendors in website design applications such as Dreamweaver, Dreamweaver itself is a system that supports several scripts for web design. either manually or manually. systemically, Dreamweaver also helps in connecting the MySQL database for data input and logging in to a website. The results are expected to add insight for the participants about website design training, and it is hoped that all application vendors have the same way so that other programming can also be learned by many people.